2018
DOI: 10.1038/s41598-018-33508-6
|View full text |Cite
|
Sign up to set email alerts
|

Oxaliplatin induces pH acidification in dorsal root ganglia neurons

Abstract: Oxaliplatin induced peripheral neurotoxicity is characterized by an acute cold-induced syndrome characterized by cramps, paresthesias/dysesthesias in the distal limbs and perioral region, that develops rapidly and lasts up to one week affecting nearly all the patients as well as by long-lasting symptoms. It has been previously shown that pharmacological or genetic ablation of TRPA1 responses reduces oxaliplatin-induced peripheral neurotoxicity in mouse models. In the present report, we show that treatment with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
21
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 40 publications
2
21
0
Order By: Relevance
“…As shown in Figure 1 A, TREK channels underwent a transient upregulation following OHP treatment. Furthermore, we also studied the effect of OHP on TRPV1 expression after 6 h of treatment and did not find any significant change (log 2 FC = 0.57 ± 0.23 relative to the untreated control, p -value = 0.19, Student’s t -test), as already reported for OHP-treated neurons after 48 h from plating [ 13 ]. These data indicate a relative specificity of action for OHP in gene expression modulation.…”
Section: Resultssupporting
confidence: 66%
See 3 more Smart Citations
“…As shown in Figure 1 A, TREK channels underwent a transient upregulation following OHP treatment. Furthermore, we also studied the effect of OHP on TRPV1 expression after 6 h of treatment and did not find any significant change (log 2 FC = 0.57 ± 0.23 relative to the untreated control, p -value = 0.19, Student’s t -test), as already reported for OHP-treated neurons after 48 h from plating [ 13 ]. These data indicate a relative specificity of action for OHP in gene expression modulation.…”
Section: Resultssupporting
confidence: 66%
“…Figure 3 A shows the single-channel currents recorded at a holding potential of 40 mV in an OHP-treated neuron before and during the perfusion of the high potassium solution containing 10 μM nigericin at pH 7.4. In these ionic conditions, nigericin was generated in neurons with an acidic pH i , a net efflux of H + that set its value near 7.4 [ 13 ]. Following the perfusion with nigericin, the patch activity NP o decreased from 0.57 ± 0.19 to 0.08 ± 0.11 ( N being the number of channels in the patch and P o the channel open-state probability), in agreement with a high sensitivity of these channels to acidic intracellular pH.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Confocal laser scanning microscopy (CLSM) showed that the FITC‐decorated AFeNPs@CAI nanoparticles could be engulfed by MB231 cells after coculturing for 4 h with strong green fluorescence (Figure S6, Supporting Information). Then we used BCECF‐AM, a pH‐sensitive probe, which decreases its fluorescence emission intensity with decreasing pH to show the change of pH intracellular . As shown in Figure d, MB231 cells in the control group displayed the strongest green fluorescence compared with AFeNPs@PA and AFeNPs@CAI group within 2 h both hypoxia and normoxia.…”
Section: Resultsmentioning
confidence: 99%